Design of NLP-Based Chatbot for Academic Services at Politeknik Negeri Medan - Sulistianingsih, Indri; Ginting, Ramadhanu; Rizka, Ade; Siregar, Brema Arihta (Electronic Integrated Computer Algorithm Journal, 2026)
The development of artificial intelligence technology has encouraged the use of chatbots in various sectors, including higher education. These chatbots can increase interaction, provide learning support, and facilitate the delivery of information automatically. This study aims to design a chatbot that functions as a virtual assistant in an educational environment, with an emphasis on increasing interaction between users and the system. The methods used include a systematic approach in designing interfaces, natural language processing (NLP), and testing the responsiveness of chatbots to user needs. From the literature review conducted, it is evident that chatbots make a positive contribution to learning motivation, student engagement, and the efficiency of the learning process, especially in the context of online learning. However, the current system is limited to predefined academic queries and does not yet handle complex academic advising, financial inquiries, or counseling support. The hope of this study is to provide guidance in developing educational chatbots that are effective, flexible, and able to adapt to user needs in the post-pandemic era.